Production of bio-gas (In urban areas using different types of wastes) - Patel, Chandramani; Kumar, Gaurav; Upadhyay, Arun Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The focus of the research paper is to investigate the importance of biogas as an alternative energy sources in urban area. Urban waste, including wastewater treatment plants, food waste from households and businesses, yard clippings, human wastes, vegetable market wastes, and non-recyclable paper, will create biogas under the right conditions. Food waste from grocery stores, restaurants, cafeterias and homes contains energy and valuable nutrients. These wastes of specific area should collect in single tank and use them in bio-gas production. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->